2013
DOI: 10.1103/physrevlett.110.028102
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of DNA Capture by a Solid-State Nanopore

Abstract: A solid-state nanopore can electrophoretically capture a DNA molecule and pull it through in a folded configuration. The resulting ionic current signal indicates where along its length the DNA was captured. A statistical study using an 8 nm wide nanopore reveals a strong bias favoring the capture of molecules near their ends. A theoretical model shows that bias to be a consequence of configurational entropy, rather than a search by the polymer for an energetically favorable configuration. We also quantified th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
111
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 19 publications
18
111
1
Order By: Relevance
“…Nanopores have provided a method to investigate various concepts in polymer physics such as polymer translocation through pores 24,25 , the Zimm relaxation time 25,26 , and the polymer capture process 27,28 . In nanopore sensing, biomolecules in an aqueous solution are placed into one of two reservoirs separated by a 20 nm thick membrane containing a nanometer scale pore (Figure 1).…”
Section: Abstract: Dna Knots Nanoporementioning
confidence: 99%
See 1 more Smart Citation
“…Nanopores have provided a method to investigate various concepts in polymer physics such as polymer translocation through pores 24,25 , the Zimm relaxation time 25,26 , and the polymer capture process 27,28 . In nanopore sensing, biomolecules in an aqueous solution are placed into one of two reservoirs separated by a 20 nm thick membrane containing a nanometer scale pore (Figure 1).…”
Section: Abstract: Dna Knots Nanoporementioning
confidence: 99%
“…Most nanopore experiments are carried out in 1M KCl 25,26,27,28 , where most observed knots have a duration (τ) of 15 µs at 100 mV, indicating that their detection is at the edge of what is resolvable (Supplementary Section 4). For this reason the majority of the experiments presented in this study are carried out in solutions of 2M or 4M LiCl, which as we have previously shown, can increase the translocation time of DNA by a factor of 7x or 10x respectively, relative to 1M KCl 35 .…”
Section: Ionic Current Signatures Of Dna Knotsmentioning
confidence: 99%
“…Nanopore sensors have enabled fundamental studies on single biopolymers [3][4][5][6][7][8][9] and show promise for use in a variety of biosensing applications [10][11][12][13][14][15][16][17][18][19] . Nanopores are particularly well suited for probing chemical interactions between DNA and other molecules [20][21][22] , because these interactions often substantially modify the structure of a DNA molecule.…”
mentioning
confidence: 99%
“…By contrast, double-stranded DNA (dsDNA) has a persistence length of only B50 nm 29 . It is flexible enough to form hernias at the mouth of a voltage-biased nanopore, and translocate in a folded configuration 30 . Folded configurations are presumably suppressed when P exceeds some threshold.…”
mentioning
confidence: 99%